Use of a multiserver architecture for enabling access to a complex medical information system at any time and from anywhere. - Gusev AV (British Journal of Healthcare Computing & Information Management, 2006)
The article outlines the multiserver architecture of a complex medical information system (MIS), focusing on the advantages of dividing workloads between several servers by physical division of databases and increasing MIS accessibility and efficiency by mirroring. The upgrading of the geographically distributed MIS database (DB) in order to increase the system's efficiency and provide offline access to the MIS DB is described.